Silicon-mediated Improvement in Plant Salinity Tolerance: The Role of Aquaporins - Rios, Juan J.; Martínez-Ballesta, Maria C.; Ruiz, Juan M.; Blasco, Begoña; Carvajal, Micaela (Frontiers in Plant Science, 2017)
Silicon (Si) is an abundant and differentially distributed element in soils that is believed to have important biological functions. However, the benefits of Si and its essentiality in plants are controversial due to differences among species in their ability to take up this element. Despite this, there is a consensus that the application of Si improves the water status of plants under abiotic stress conditions. Hence, plants treated with Si are able to maintain a high stomatal conductance and transpiration rate under salt stress, suggesting that a reduction in Na+ uptake occurs due to deposition of Si in the root. In addition, root hydraulic conductivity increases when Si is applied. As a result, a Si-mediated upregulation of aquaporin (PIP) gene expression is observed in relation to increased root hydraulic conductivity and water uptake. Aquaporins of the subclass nodulin 26-like intrinsic proteins (NIPs) are further involved in allowing Si entry into the cell. Therefore, on the basis of available published results and recent developments, we propose a model to explain how Si absorption alleviates stress in plants grown under saline conditions through the conjugated action of different aquaporins